DEAD‐Box Helicase 6 Blockade in Brain‐Derived Aβ Oligomers From Alzheimer's Disease Patients Attenuates Neurotoxicity - Xiaoxu Wang; Lu Dai; Na Wu; Donghui Wu; Xinyuan Wang; Xia Meng; Qilei Zhang; Jing Lu; Xiaoxin Yan; Jing Zhang; Baian Chen (MedComm)
ABSTRACT There are no effective curative treatments for Alzheimer's disease (AD), the most prevalent form of dementia. Amyloid‐beta (Aβ) oligomers are considered key neurotoxic molecules that trigger AD. Recent studies have shown that direct antibody targeting of Aβ oligomers is beneficial for early AD patients; however, serious side effects (e.g., brain hemorrhage, edema, and shrinkage) persist. Considering that Aβ oligomers readily bind to other proteins, contributing to neurotoxicity and AD onset, those proteins could represent alternative therapeutic targets. However, proteins that bind to Aβ oligomers in the brains of AD patients have not yet been identified. In this study, we identified four proteins (DDX6, DSP, JUP, and HRNR) that bind to Aβ oligomers derived from the brains of AD patients. Intriguingly, among these four proteins, only the blockade of DEAD‐box helicase 6 (DDX6) in human‐derived Aβ oligomers attenuated their neurotoxicity both in vitro and in vivo. Mechanistic analysis revealed that DDX6 promotes the formation of Aβ oligomers, likely due to DDX6 bind to Aβ oligomers at four distinct sites. These findings suggest that DDX6 could serve as a potential therapeutic target to reduce the neurotoxicity of Aβ oligomers in the brain and prevent the progression of AD.